Pengaruh Variasi Temperatur Curing Terhadap Kekuatan Tarik Biokomposit Getah Damar Diperkuat Serbuk Kayu Jati: Effect of Curing Temperature Variation on the Tensile Strength of Damar Resin Biocomposites Reinforced with Teak Wood Powder - Ngurah Putu Putra Adnyana; I Nyoman Pasek Nugraha; Kadek Rihendra Dantes; Kadek Sutrisna (Universitas Pendidikan Ganesha, 2026)
This study aimed to analyze the effect of curing temperature variation on the tensile strength of dammar resin-based biocomposites reinforced with teak wood powder. The biocomposite consisted of 60% dammar resin as the matrix and 40% teak wood powder as the reinforcement. The curing temperatures were varied at 50°C, 100°C, and 150°C with a holding time of 1 hour. The specimens were fabricated according to the ASTM D3039 standard and tested using a Universal Testing Machine (UTM). The evaluated parameters included tensile strength, strain, elastic modulus, and fracture characteristics. The results showed that increasing the curing temperature improved the mechanical properties of the biocomposite. The average tensile strength at curing temperatures of 50°C, 100°C, and 150°C was 408.64 kPa, 507.37 kPa, and 534.80 kPa, respectively. The elastic modulus also increased from 31,153.33 kPa at 50°C to 429,003.33 kPa at 150°C. Fracture surface observations indicated that higher curing temperatures enhanced the interfacial bonding between the dammar resin matrix and teak wood powder, resulting in improved tensile performance. Therefore, a curing temperature of 150°C produced the best mechanical properties and is recommended as the optimum curing condition for dammar resin biocomposites reinforced with teak wood powder.